ASSESSMENT OF EFFICIENCY OF OBSTETRIC CARE ORGANIZATION MODEL IN RUSSIAN FEDERATION - O. S. Filippov; E. V. Guseva (IRBIS LLC, 2016)
In order to analyze the system of medical care organization during pregnancy and labor, and to evaluate the effect of organization of obstetric and resuscitation aid to females on the parameter of maternal mortality (MM), the updated information on organization of medical care for pregnant, maternity patients and new mothers over the period of 2006 2009 in 85 subjects of RF, has been assessed. The assessment was carried out by level I obstetric aid institutions (obstetric departments of central district hospitals), level II institutions (inter regional and urban maternity hospitals, perinatal centers, maternity departments of urban multidisciplinary hospitals) and level III institutions (provincial, regional and republican perinatal centers, maternity homes, teaching hospital clinics and federal scientific research institutes). A statistically significant, strong and direct relationship was found between the percentage of obstetric beds in the level I obstetric institutions (r = 0.81), fraction of labors in the level I inpatient institutions (r = 0.99), percentage of beds for pregnant and maternity patients not provided for by round the clock on call service by hospital obstetrician gynecologist (r = 0.84) on the one hand, and the MM parameter on the other. There was a strong inverse relationship between the fraction of labors occurred in the level III obstetric care institutions (r = 0.89), availability of regional maternity home (department), perinatal center (r = 0.90), obstetric distance consultancy center (r = 0.89), percentage of obstetric care institutions equipped with departments (wards) of resuscitation and intensive care (r = 0.99), on the one hand, and the MM parameter on the other. Therefore, for prophylaxis and MM reduction it is necessary to implement modern organizational technologies of providing medical care for pregnant, maternity patients and new mothers based on a three level system organization, in which the perinatal centers take the leading role.